1st Street food store planned - Wildermuth, Todd (Raton, NM Raton Range, 1994)
Article is about David Manfredi hoping to open a bulk food store in the old Gamble's Building on First Street.
Newspaper article + Photograph of David Manfredi
Master list item #: 56
File location is in the Raton file Cabinet
Keywords: Manfredi, David; Sharts, Wally; Keep's Wholesale; Gamble's building; Swastika Fuel Company; Bulk Food Stores; Food Stores; Local Business; Wholesales; Raton, New Mexico; First Street Business